Penerapan Model Pembelajaran Flipped Classroom Dalam Mata Pelajaran SKI XI MA PPMTI Bayur - Riyadi, Fadil; I, Iswantir (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
The background of this thesis is the fact that teachers control teaching and learning activities, students only listen, and teachers only use the lecture method. It is also evident that some students are not very eager to engage in the learning process. The author is therefore curious in investigating the application of the flipped classroom learning paradigm to the SKI XI MA PPMTI Bayur topic. This kind of study, which aims to characterize, explain, and interpret a phenomenon that occurs based on relevant facts in the field, employs descriptive qualitative research techniques. Together with supporting informants, the Class XI MAS PPMTI Bayur students and the Class XI MAS PPMTI Bayur SKI instructor, are essential informants. The author did observations, conducted interviews, and documented in order to gather data. Following data collecting, analysis and processing of the data were done. After that, triangulation is used to construct a validity assurance method. Students are expected to study the material for the next meeting on their own at home before the in-person meeting. They can watch instructional videos uploaded by others or those created by the teacher. They can also form groups to have discussions. Additionally, teachers prepare questions to be asked. Students are made aware that the exercise they are doing is a learning process and that educators serve as facilitators in helping students learn and solve problems related to material by giving a quiz or test at the end.